It is green, but is it fair? Investigating consumers’ fairness perception of green service offerings - Yuen, Kum Fai (2018)
With the prevailing green skepticism, consumers tend to devalue firms' environmental claims and raise concerns on service fairness of green offerings. Applying theoretical insights from fairness literature to the context of green consumerism, this study examines the antecedents, consequences, and moderators of fairness perceptions in consumers' response to green service offerings. A scenario-based experiment is conducted (n 1⁄4 600) for data collection and the data are analyzed using Structural Equation Modelling (SEM). It is found that consumers' inferred relative profit (PRO) of the firm negatively influences their perceived fairness (FAI), whereas a positive inference on firms' motives (MOT) leads to a fairer perception by consumers. Furthermore, to a certain extent, firms' commitment to environment (F-ENV) and con- sumers' personal environmental commitment (C-ENV) serve as effective moderators that enhance consumers' fairness perception. However, multi-sampling moderation tests suggest that PRO remains as a persistent source of the unfairness perception regardless of the levels of C-ENV. It is only when F-ENV is present then consumers' unfairness perception would be attenuated. This study contributes to literature with a unique theoretical perspective of service fairness in examining consumers' behavioral response to green service offerings. Also, it provides practical insights to managing the effectiveness of firms' green initiatives by placing consumers’ fairness as a critical concern.